THE ROLE OF THE REGIONAL DEVELOPMENT PLANNING AGENCY (BAPPEDA) IN THE PARTICIPATIVE DEVELOPMENT PLANNING PROCESS - Muhammad Fadli (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal